Nutrition care in pediatric patients with severe diabetic ketoacidosis, hyperglycemia and suspected type 1 diabetes - Wahyu Dwi Suzanti; Sukmawati Sukmawati; Suriani Rauf; Musyawarah Thahir (Institute of Computer Science (IOCS), 2026)
Diabetes mellitus (DM) is a chronic disease with an increasing prevalence among children. Type 1 DM, the most common form in pediatrics, results from autoimmune destruction of pancreatic β-cells, leading to absolute insulin deficiency. Diabetic ketoacidosis (DKA) is a life-threatening acute complication that may cause acute kidney injury (AKI), electrolyte imbalance, and respiratory distress. This case study applied the Standardized Nutrition Care Process (SNCP), including nutritional assessment, diagnosis, intervention, monitoring, and evaluation, in a 1-year-3-month-old girl diagnosed with severe DKA, suspected type 1 DM, severe dehydration, community-acquired pneumonia, anemia, hypokalemia, azotemia, KDIGO stage II AKI, and marasmus-type malnutrition. Nutritional assessment showed severe malnutrition (weight-for-length Z-score < −3 SD) with clinical signs of iga gambang. Nutrition diagnoses included altered nutrition-related laboratory values associated with endocrine dysfunction, evidenced by HbA1c 11.1%, random blood glucose >200 mg/dL, urea 123 mg/dL, creatinine 0.9 mg/dL, hemoglobin 10.1 g/dL, and estimated glomerular filtration rate (eGFR) 48%, as well as disease-related pediatric malnutrition characterized by low weight-for-length, mid-upper arm circumference (MUAC) 83.3%, inadequate intake (<50% of requirements), and clinical malnutrition signs. Nutritional intervention consisted of a 1,100-kcal diabetic diet with enteral formula via nasogastric tube and chopped porridge orally. The patient's nutritional intake gradually improved to an adequate level during hospitalization, although significant changes in nutritional status were not observed because of the short intervention period. Nutrition education was provided to the family to support long-term management. This case highlights the importance of individualized, gradual, and closely monitored nutritional therapy as part of multidisciplinary care to optimize recovery and prevent further complications in pediatric patients with type 1 DM and severe DKA.